Penerapan Enterprise Resource Planning Dalam Supply Chain Management Pada Minimarket Family Cukir - Raden Johnny Hadi Raharjo; Alya Nur Azizah; Adi Bimantoro; Vandra Renanda Zulfian; Erni Prasetyo (Jurnal Ilmiah Wahana Pendidikan, 2023)
Based on the discussion, it can be concluded that the implementation of Enterprise Resource Planning (ERP) in Supply Chain Management (SCM) can be an effective solution to address the supply chain management issues faced by Minimarket Family Cukir. The main problem identified is the inconsistency between the recorded inventory data in the system and the physical stock in the warehouse and store. This can result in significant financial and operational losses. To overcome these issues, several recommended steps have been suggested, including the implementation of Standard Operating Procedures (SOP) to provide clear and detailed guidelines for employees in inventory management. This includes supervision, record-keeping, updating, and monitoring of stock. Additionally, the utilization of an ERP software, specifically Odoo, is recommended to optimize the inventory management processes of Minimarket Family Cukir for greater efficiency. Lastly, improving human resource management is crucial to minimize incidents of human error and ensure adherence to established SOP. The implementation of these improvement measures measures will help them overcome their supply chain management challenges and enhance the effectiveness and efficiency of their inventory management.